A new discordancy test on a regression for cylindrical data - Nurul Hidayah Sadikon,; Adriana Irawati Nur Ibrahim,; Ibrahim Mohamed,; Dharini Pathmanathan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
A cylindrical data set consists of circular and linear variables. We focus on developing an outlier detection procedure for cylindrical regression model proposed by Johnson and Wehrly (1978) based on the k-nearest neighbour approach. The procedure is applied based on the residuals where the distance between two residuals is measured by the Euclidean distance. This procedure can be used to detect single or multiple outliers. Cut-off points of the test statistic are generated and its performance is then evaluated via simulation. For illustration, we apply the test on the wind data set obtained from the Malaysian Meteorological Department.